A Concise Review: Sustained Release Tablets - Pachori, Abhitul; Negi, Anjali (Journal of Neonatal Surgery, 2025)
Sustained release Tablets describes a pharmaceutical dosage form formulated to retard the release of therapeutic drug so that it remains in the systems. Once dose reaches maximum level, the concentration of the medicine in the body releases slowly, so that it takes a long time to fall below the therapeutic range.Improving patient compliance, while increasing bioavailability and effectiveness, is a fundamental concept of the SDDS..It works on various mechanisms to control drug emission rate